Peningkatan Kompetensi Publikasi Ilmiah Mahasiswa melalui Pendampingan Penggunaan Mendeley dan Open Journal System - Rita Sari (Seulanga: Jurnal Pengabdian Kepada Masyarakat, 2026)
Scientific publication is an important indicator of academic culture development in higher education institutions. However, many postgraduate students still face challenges in reference management and article submission through the Open Journal System (OJS). This community service program aimed to enhance students’ competencies in using Mendeley reference management software and in submitting scholarly articles through OJS. The program employed a Service-Learning approach that integrated learning activities, mentoring, hands-on practice, and reflection. The activity was conducted online via Zoom Meeting on April 27, 2024, involving students of the Master's Program in Islamic Education at IAIN Langsa. The implementation stages included needs assessment, instructional sessions, Mendeley demonstrations, OJS submission simulations, independent practice, and program evaluation. The results demonstrated significant improvements in participants’ abilities to manage references, generate automatic citations, compile bibliographies, and navigate the OJS platform. The tangible impact of the program was reflected in the publication of 14 scientific articles in the Sagoe Literasi Journal during the 2024–2025 period, consisting of three articles in Volume 1 Issue 1 (2024), three articles in Volume 1 Issue 2 (2024), three articles in Volume 2 Issue 1 (2025), and five articles in Volume 2 Issue 2 (2025). These findings indicate that practice-based mentoring effectively improves students’ scientific publication competencies while strengthening academic culture and publication productivity in higher education institutions